2016
DOI: 10.1111/evj.12601
|View full text |Cite
|
Sign up to set email alerts
|

Measurement of distal limb sub‐bandage pressure over 96 hours in horses

Abstract: Pressure distribution was not uniform. The DLP pressures were maintained for a 24 h period. The DLC maintained high pressures for 96 h, but a significant decrease in pressure occurred between 6 and 12 h. Providing there are no other reasons to change a bandage, a 4 day interval between bandages may be appropriate if maintaining distal limb compression is the principal indication.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
13
0
4

Year Published

2016
2016
2024
2024

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(19 citation statements)
references
References 15 publications
2
13
0
4
Order By: Relevance
“…C‐ELA exerted pressures above the human therapeutic pressure range for edema reduction and were able to maintain this pressure during walking. In addition, in previous work, our group found that compressing a pillow pad with a polo wrap over the distal limb produced mean sub‐bandage pressures that ranged from 75 mmHg to 85 mmHg over a 24 hour period . Anecdotal experience from our hospital provides evidence that polo/pillow pad wraps are efficacious in reducing distal limb edema, and it is reasonable to assume that C‐ELA pressures, although slightly less than those of the polo wrap pressures, are equally efficacious for carpal edema.…”
Section: Discussionmentioning
confidence: 64%
See 3 more Smart Citations
“…C‐ELA exerted pressures above the human therapeutic pressure range for edema reduction and were able to maintain this pressure during walking. In addition, in previous work, our group found that compressing a pillow pad with a polo wrap over the distal limb produced mean sub‐bandage pressures that ranged from 75 mmHg to 85 mmHg over a 24 hour period . Anecdotal experience from our hospital provides evidence that polo/pillow pad wraps are efficacious in reducing distal limb edema, and it is reasonable to assume that C‐ELA pressures, although slightly less than those of the polo wrap pressures, are equally efficacious for carpal edema.…”
Section: Discussionmentioning
confidence: 64%
“…Intra‐applicator bandage pressure variation has been established in human medicine and could account for some of the pressure differences in this study . The distal limb bandages were not tested by walking in the current study because we have previously shown that DLC maintain high pressures for 96 hours in horses confined to a stall . We believe that ambulation within a stall exceeds the short walk performed in the current study.…”
Section: Discussionmentioning
confidence: 87%
See 2 more Smart Citations
“…In this study Nathan Canada and colleagues at Kansas State University, USA, examined the pressures exerted by distal limb bandages in horses over 96 hours .…”
Section: Distal Limb Bandage Pressurementioning
confidence: 99%